Hydroponic Production Training Towards Adiwiyata Schools at Gelora Jaya Nusantara Vocational School Medan - Sri Wahyuni; Martalena Br. S. Kembaren; Noverita Sprinse Vinolina (Outline Publisher, 2025)
Environmental education is a crucial aspect in shaping a generation responsible for environmental sustainability, with the Adiwiyata Program being a strategic initiative in Indonesia to achieve this goal. The Adiwiyata Program encourages schools to create a clean, healthy, and sustainable environment, and to instill an environmental culture through real practices involving all school elements. One modern agricultural method that can be effectively integrated into environmental education in schools is hydroponic cultivation. Hydroponics, as a soilless farming technique utilizing nutrient-rich solutions in water, offers efficiency in water and land use, and reduces the risk of pests and diseases. These advantages make it ideal for schools with limited land or those wishing to maximize space utilization. SMK Gelora Jaya Nusantara Medan, as a vocational institution, has great potential to implement hydroponics as part of Adiwiyata, especially given the challenge of limited green space in urban Medan. Hydroponic training can equip students and teachers with technical knowledge, foster environmental awareness, entrepreneurship, and self-reliance through active involvement in cultivation. This initiative aligns with the Adiwiyata vision to create an environmentally cultured school environment and produce graduates who care about global issues. Hydroponic projects also teach about the water cycle, plant nutrition, and the positive impacts of sustainable agriculture on food security and climate change mitigation. This community service discusses the implementation and impact of hydroponic training at SMK Gelora Jaya Nusantara Medan as a concrete step towards becoming an Adiwiyata School, and analyzes the increased environmental awareness within the school community.